Hydrological connectivity from glaciers to rivers in the Qinghai–Tibet Plateau: roles of suprapermafrost and subpermafrost groundwater - R. Ma; R. Ma; Z. Sun; Z. Sun; Y. Hu; Q. Chang; S. Wang; W. Xing; M. Ge (Hydrology and Earth System Sciences, 2017)
The roles of groundwater flow in the hydrological cycle within the alpine area characterized by permafrost and/or seasonal frost are poorly known. This study explored the role of permafrost in controlling groundwater flow and the hydrological connections between glaciers in high mountains and rivers in the low piedmont plain with respect to hydraulic head, temperature, geochemical and isotopic data, at a representative catchment in the headwater region of the Heihe River, northeastern Qinghai–Tibet Plateau. The results show that the groundwater in the high mountains mainly occurred as suprapermafrost groundwater, while in the moraine and fluvioglacial deposits on the planation surfaces of higher hills, suprapermafrost, intrapermafrost and subpermafrost groundwater cooccurred. Glacier and snow meltwaters were transported from the high mountains to the plain through stream channels, slope surfaces, and supra- and subpermafrost aquifers. Groundwater in the Quaternary aquifer in the piedmont plain was recharged by the lateral inflow from permafrost areas and the stream infiltration and was discharged as baseflow to the stream in the north. Groundwater maintained streamflow over the cold season and significantly contributed to the streamflow during the warm season. Two mechanisms were proposed to contribute to the seasonal variation of aquifer water-conduction capacity: (1) surface drainage through the stream channel during the warm period and (2) subsurface drainage to an artesian aquifer confined by stream icing and seasonal frost during the cold season.